(untitled) (Research, Society and Development, 2024)
In this case report, the management of a patient with sickle cell disease who developed cardiopulmonary arrest and pneumonia caused by an encapsulated germ is described. The patient was attended by a multidisciplinary team that implemented life support measures and specific antimicrobial treatment. The importance of early detection of complications in patients with sickle cell disease and the need for a comprehensive approach to their management is highlighted. This case highlights the relevance of close monitoring and timely treatment in critical situations for patients with this hematological disease. The importance of interdisciplinary collaboration and continuous follow-up to improve clinical outcomes in patients with sickle cell disease is emphasized.